Anesthetic effects of clove (Eugenia aromaticum) seed extract on Clarias gariepinus (Burchell, 1822) fingerlings under semi-arid conditions - Diyaware Mohammed Y.; Suleiman Sa’adu B.; Akinwande Akinlolu A.; Aliyu Mohammed (Journal of Agricultural Sciences (Belgrade), 2017)
The anesthetic effects of clove (Eugenia aromaticum) seed extract on Clarias gariepinus fingerlings were investigated under semi-arid conditions. Various concentrations of the clove seed extract at 25.0, 50.0, 75.0, 100.0, 125.0 and 150.0mg per liter of water were used for the experiment. Each concentration was tested on a group of 10 Clarias gariepinus fingerlings (24.13-25.30g in weight and 5.97-7.00 cm in length) in glass aquariums. There was a decrease in induction time as the concentration of the clove seed extract increased. Fingerlings treated with 150mg/l of the extract produced the shortest induction time (2.28±0.15 minutes), followed by fish treated with 100 and 125mg/l (3.31±0.55 and 3.07±0.07 minutes, respectively). The longest induction time (10.60±0.98, 7.52±0.25 and 5.96±1.17 minutes) was observed in fingerlings sedated with 50, 25 and 75mg/l, respectively. Recovery was significantly faster (2-3.92 minutes) in fish treated with lower dosages (25 to 125mg/l) of the clove seed extract. Mortality rates after 24 hours of recovery were higher (4.79±0.25 and 3.10±0.54%) in fish anesthetized with higher (150 and 125mg/l) concentrations of the clove seed extract, respectively.